Mangrove Flora and Fauna in Sundarbans and Their Significance in a Global Perspective - Jayanta Kumar Mallick (Surviving Sundarbans: Tragedy and Hope, Edition 1, 2025)
Sundarbans, the largest tidal mangrove ecosystem, aka a Tiger Conservation Landscape of global priority, supporting rich biological diversity and providing invaluable services, is highly threatened due to natural and anthropogenic factors, such as historical overexploitation, hunting/poaching, series of natural disasters and decadal climate change dimensions. In total, 7,533 micro- and macro-lifeforms or unique biodiversity have been recorded in the [Fringe mangrove forests and non-mangrove hinterland (reclaimed areas)] Biosphere Reserve (SBR), spread over 9,630 km2, on the basis of a literature (published and grey) survey and a longitudinal field investigation, which were conducted by using Multistage Purposive Sampling techniques with a predesigned format (for quantitative and qualitative assessment), involving professionals, researchers, NGOs, designated forest department officials and staff concerned, as well as communities living in the fringe areas and directly or indirectly depending on the forest resources for their livelihood. The Indian counterpart of the only mangrove tiger land in the world is spread over 4,264.53 km2 of forests or in-situ conservation areas, such as uninhabited reserved forests, national parks (core/critical tiger habitat), wildlife sanctuaries and buffer areas. The transitional zone (5,365.47 km2) is densely populated (c.4 million), the impacts of agriculture, hydrological changes, illegal fishing including shrimp farming, pollution and climate change have intensified during the 21st century. Consequently, the vulnerable mangrove forests have been evaluated as ‘endangered’ in a 2020 assessment under the IUCN Red List of Ecosystems framework. At this stage, the concerted management efforts within and beyond the conservation areas of SBR are based on the restoration of the unique mangrove ecosystem and the conservation of its extant biodiversity through sustainable development of the fringe population.